2015
DOI: 10.1590/1678-4162-8221
|View full text |Cite
|
Sign up to set email alerts
|

Plasma PGFM and progesterone concentrations, luteolysis moment and estrous cycle length in Nelore cows submitted to uterine biopsies

Abstract: In this study, endometrial samples were collected in 14 Nelore cows on days zero (ovulation), five, nine, thirteen and nineteen of the estrous cycle (biopsy group), and in 15 females these collections weren't performed (control group). Biopsies were done on the uterine horn endometrium contralateral to the ovary with corpus luteum. Blood samples were taken at -24, -16, -8, 0 +8, +16 and +24 hours in relation to progesterone drop (<1ng/mL, zero moment) and evaluated for 13, 14-dihydro-15-keto prostaglandin F2-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…While it appears that biopsy does not have a substantial negative effect on oestrous cycle length or conceptus survival there is release of endometrial PGF2α after the procedure. Martin et al, (2015) found that on the day of luteolysis (Day 18), PGFM concentrations in biopsied heifers were higher compared to non-biopsied controls (83.4 ±16.3 vs. 55.4 ±16.4, respectively P<0.05). …”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…While it appears that biopsy does not have a substantial negative effect on oestrous cycle length or conceptus survival there is release of endometrial PGF2α after the procedure. Martin et al, (2015) found that on the day of luteolysis (Day 18), PGFM concentrations in biopsied heifers were higher compared to non-biopsied controls (83.4 ±16.3 vs. 55.4 ±16.4, respectively P<0.05). …”
Section: Introductionmentioning
confidence: 90%
“…While most of the studies have shown CL lifespan is not affected by either single or repeated endometrial biopsies during an oestrous cycle (Mann and Lamming, 1994, Boos et al, 1996, Katagiri and Takahashi, 2004 or during early pregnancy (Meikle et al, 2005, Martin et al, 2015 one study showed oestrous cycles may be shortened after performing two endometrial biopsies in the same cycle (Zaayer and Van der Horst, 1986). While it appears that biopsy does not have a substantial negative effect on oestrous cycle length or conceptus survival there is release of endometrial PGF2α after the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations